Ay allele promotes azoxymethane‐induced colorectal carcinogenesis by macrophage migration in hyperlipidemic/diabetic KK mice. Issue 7 (25th May 2013) - Ito, Kumiko; Ishigamori, Rikako; Mutoh, Michihiro; Ohta, Toshihiro; Imai, Toshio; Takahashi, Mami
Abstract : The incidence of colorectal cancer has been increasing and is associated with obesity and diabetes. We have found that type 2 diabetes model KK‐ A y /TaJcl (KK‐ A y ) mice develop tumors within a short period after treatment with azoxymethane (AOM). However, factors that contribute to the promotion of carcinogenesis have not been clarified. Therefore, we looked at the genetic background of KK‐ A y, including two genetic characteristics of KK/TaJcl (KK) mice and C57BL/6J‐Ham‐ A y /+ ( A y ) mice, compared with other non‐obese and non‐diabetic mouse strains C57BL/6J and ICR, and induced colorectal premalignant lesions, aberrant crypt foci (ACF), and tumors using AOM (150 μg/mouse/week for 4 weeks and 200 μg/mouse/week for 6 weeks, respectively). The mice with a diabetes feature, KK‐ A y and KK, developed significantly more ACF, 67 and 61 per mouse, respectively, whereas ICR, A y, and C57BL/6J mice developed 42, 24, and 18 ACF/mouse, respectively, at 17 weeks of age. Serum insulin and triglyceride levels in KK ‐ A y and KK mice were quite high compared with other non‐diabetic mouse strains. Interestingly, KK‐ A y mice developed more colorectal tumors (2.7 ± 2.3 tumor/mouse) than KK mice (1.2 ± 1.1 tumor/mouse) at 25 weeks of age, in spite of similar diabetic conditions. The colon cancers that developed in both KK‐ A y and KK mice showed similar activation of β‐catenin signaling. However, mRNA levels of inflammatory factors related to the activation of macrophages were significantly higher in colorectal cancer of KK‐ A y mice than in KK. These data indicate that factors such as insulin resistance and dyslipidemia observed in obese and diabetic patients could be involved in susceptibility to colorectal carcinogenesis. In addition, increase of tumor‐associated macrophages may play important roles in the stages of promotion of colorectal cancer.